Poly(acrylamide-homocysteine thiolactone) as a synthetic platform for the preparation of polymeric ionic liquids by post ring-opening-orthogonal modifications. Issue 33 (26th July 2017) - Montolio, Silvia; Zagorodko, Oleksandr; Porcar, Raúl; Isabel Burguete, M.; Luis, Santiago V.; Tenhu, Heikki; García-Verdugo, Eduardo
Abstract : Post-modification of Poly(Acrylamide-Homocysteine Thiolactone) provides a variety of advanced polymeric materials with different morphologies and structural diversity. Abstract : Poly(Acrylamide-Homocysteine Thiolactone) (PAHT) obtained by RAFT polymerisation can be used as a starting material for the synthesis, through its post modification, of a variety of advanced polymeric materials with different morphologies and a significant structural diversity. The examples here presented illustrate the utility of this approach for the preparation of functionalised polymers containing Ionic Liquid-like units (IL-like). These Polymeric Ionic Liquids (PILs) can be designed and obtained with a careful control of their structural elements according to the needs for a specific application.